Long‐term safety and efficacy of lemborexant in subjects with irregular sleep‐wake rhythm disorder and Alzheimer's disease dementia: Human/Human trials: Other. (7th December 2020) - Moline, Margaret; Bsharat, Mohammad; Cheng, Jocelyn
Abstract: Background: Irregular Sleep‐Wake Rhythm Disorder (ISWRD) is a common circadian rhythm sleep disorder among individuals with Alzheimer's disease dementia (AD‐D). The dual orexin receptor antagonist lemborexant (LEM) is approved in the US and Japan for insomnia, and is under investigation for ISWRD. Effects of LEM on clinical measures of ISWRD were evaluated in patients with mild‐moderate AD‐D in a Phase 2 proof‐of‐concept and dose‐finding clinical study (NCT03001557; E2006‐G000‐202). LEM improved circadian variables, helped consolidate nighttime sleep, and was well tolerated, over 1 month. Safety and efficacy data over the Core and long‐term open‐label Extension Phases are reported for subjects who entered the Extension Phase. Methods: This randomized, double‐blind, multicenter, global, placebo (PBO)‐controlled parallel group study enrolled subjects (aged 60‐90y) who met DSM‐5 criteria for ISWRD and had mild‐moderate AD‐D. In the Core Phase, subjects were randomized to PBO or LEM (2.5mg, 5mg [LEM5], 10mg [LEM10], or 15mg [LEM15]) for 28 days. During the Extension Phase, eligible subjects initially received open‐label LEM10, with option of adjusting the dose to LEM5 or LEM15. Caregivers completed the Sleep Disorders Inventory (SDI), which assesses sleep‐related disturbances. SDI total score (SDI‐ts) was derived as the product of the average of the frequency ratings and the average of the severity ratings (range: 0–12 [worst]). Results: Twenty‐five subjects entered the Extension Phase. In these subjects, treatment emergent adverse events (TEAEs) were reported in 16(64%) subjects over the Core and Extension Phases (1‐14 months). Serious TEAEs were reported in 3(12%) subjects; no deaths were reported. TEAEs led to dose adjustment in 4(16%) subjects. The most common TEAEs (incidence >10%) were nasopharyngitis (n=4;16%), fall (n=3;12%), and somnolence (n=3;12%). In subjects who received a modal dose of LEM10 (Core and Extension Phases [n=17]), mean(SD) SDI‐ts was 0.72(0.75) at baseline (n=12). Mean(SD) change from baseline (CFB) in SDI‐ts at Day 29 (n=12) was −0.14(0.63). In the Extension Phase, mean(SD) CFB in SDI‐ts was −0.37(0.50) at Day 133 (n=14) and −0.12(0.81) at Day 223 (n=12). Conclusions: In subjects with AD‐D and ISWRD treated with LEM10, moderate improvement in SDI‐ts continued to be observed over time. LEM was well tolerated over 1‐14 months. Support: Eisai Inc.